A novel method for calculating the light energy distribution in building space. (5th October 2020) - Fu, Jundong; Chen, Qing
In lighting design in buildings, the conventional algorithms may cause significant calculation error of light energy distribution and may not ensure illumination uniformity. In this paper, the radiation method in computer graphics is studied, combined with formula derivation, two kinds of light energy calculation methods based on Lambert reflection model and non-Lambert reflection model are investigated, and two models: model 1 and model 2, are established for interior space of non-uniform height and non-rectangular interior space respectively. Comparing simulation results of the models with existing models in a DIALux environment, the illumination uniformity calculation error of model 1 is 30%, and the calculation error of model 2 is within 5%. In addition, parameters of the models are modulated by experiments, in order to improve the accuracy of the models. Although model 1 based on Lambert's reflection model runs fast, its accuracy needs to be improved. In the case of high simulation accuracy of spatial light environment, model 2 based on the non-Lambert reflection model is the better choice. At the same time, it is proved that the improved radiation method is feasible in calculating the light energy of interior spaces with non-uniform height and non-rectangular shape.